1976
DOI: 10.1507/endocrj1954.23.5
|View full text |Cite
|
Sign up to set email alerts
|

Increase of serum GH concentration following TRH injection in patients with primary hypothyroidism.

Abstract: SynopsisThe effect of TRH administration on serum GH was studied in 6 normal subjects, 13 patients with primary hypothyroidism and 6 thyrotoxic subjects. Although no appreciable changes of serum GH were noted in the normal subjects, TRH administration provoked an increase of serum GH in 6 out of 13 patients with primary hypothyroidism.Serum GH levels in response to TRH administration were decreased in patients who were euthyroid following treatment with a preparation of desiccated thyroid.In patients with hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0
1

Year Published

1978
1978
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 16 publications
(20 reference statements)
2
9
0
1
Order By: Relevance
“…Four of the seven children with prolonged, untreated, acquired, primary hypothyroidism (group B) responded with abnormal ("paradoxical") elevation in serum GH concentrations after TRH. This response has been reported previously in hypothyroid children (3) and adults (4). The cause for the paradoxical GH response in hypothyroidism is not known.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Four of the seven children with prolonged, untreated, acquired, primary hypothyroidism (group B) responded with abnormal ("paradoxical") elevation in serum GH concentrations after TRH. This response has been reported previously in hypothyroid children (3) and adults (4). The cause for the paradoxical GH response in hypothyroidism is not known.…”
Section: Resultssupporting
confidence: 81%
“…Two examples of these alterations are the increased PRL response to TRH (1,2) and the stimulation of GH secretion by TRH in hypothyroid children (3) and adults (4); these responses do not occur in normal subjects (5). It has been shown that many children suffering from congenital hypothyroidism manifest high serum TSH concentrations for prolonged periods despite adequate replacement therapy, clinical euthyrodism, and normal serum levels of thyroid hormones (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…The serum GH level in response to TRH injection was raised in patients with euthyroid function who had recovered from hypothyroidism following treatment with a preparation of dessicated thyroid (Hamada et al, 1976), but triiodothyronine showed no effect on GH response to TRH in patients with acromegaly (Fagilia et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…There also have been many reports suggesting that an elevation of the plasma growth hormone (GH) level could be induced after TRH injection in patients with various diseases including acromegaly or gigantism (Irie and Tsushima, 1972 ;Liuzzi et al, 1976), depression (Maeda et al 1975), renal failure (Gonzalez-Barcerna et al, 1974), primary hypothyroidism (Hamada et al, 1976) and severe liver disease (Pan.erai et al, 1977).…”
mentioning
confidence: 99%
“…Although it is well known that thyrotropin releasing hormone (TRH) stimulates both thyrotropin (TSH) and prolactin (PRL) release from the anterior pituitary in normal subjects (Anderson et al, 1971 ;Bowers et al, 1971 ;Jacobs et al, 1971), it also has been reported that in some pathological conditions such as acromegaly or gigantism (Irie and Tsushima, 1972 ;Schalch et al, 1972;Faglia et al, 1973), primary hypothyroidism (Hamada et al, 1976), anorexia nervosa (Maeda et al, 1976), mental depression (Maeda et al, 1975), chronic liver diseases (Panerai et al, 1977), alcoholic hepatitis with cirrhosis (Zanboni and ZanboniMuciaccia, 1977), liver cancer (Kamijo et al, 1980), chronic renal failure (GonzalezBarcena et al, 1973;Hasegawa et al, 1975), insulin dependent diabetes mellitus (Ceda et al, 1982), and isolated TSH deficiency (Miyai et al, 1976), TRH is able to stimulate growth hormone (GH) release.…”
mentioning
confidence: 99%